Uji Efektivitas Antiinflamasi Ekstrak Etanol Daun Pacar Air (Impatiens Balsamina L.) terhadap Tikus Putih Jantan (Rattus Norvegicus) yang Diinduksi dengan Karagenan - Melati Yulia Kusumastuti; Nurhayuna Nurhayuna; Siti Aisyah Tanjung (Pusat riset dan Inovasi Nasional, 2025)
Inflammation is a response to tissue damage due to various adverse stimuli, both chemical and mechanical stimuli and infections. One of the chemical compounds found in henna leaves is flavonoids that are efficacious as anti-inflammatory. The aim of the study was to determine the anti-inflammatory effectiveness of water henna leaf extract reviewed from a decrease in udem volume in the soles of the feet of male white rats induced by carrageenan 1%. The research method used was experimental on simplicia and ethanol extract of henna leaf (EEDPA) as well as testing the anti-inflammatory effectiveness of EEDPA. Testing of the anti-inflammatory effect was carried out on 30 male white mice induced with 1% carrageenan subplantarly. The test animal group was divided into five groups consisting of a positive group given Na-diclofenac, a negative control group given CMC, and a test group of water henna leaf ethanol extract at doses of 200 mg/kgBB, 400 mg/kgBB and 800 mg/kgBB. The parameters observed in this study were the volume of the leg udem of the test animal which was measured with a Plethysmometer every 6 hours. The data obtained was then calculated as the percent of inflammation and the percent of inflammation inhibition. Analyzed with One Way ANOVA with a 95% confidence rate. The results of the effectiveness test showed that EEDPA had an anti-inflammatory effect in carrageenan-induced male white rats. Optimal effectiveness indicated by the dose showed that EEDPA at a dose of 800 mg/kgBB